A belief‐desire‐intention agent architecture for partner selection in peer‐to‐peer live video streaming applications. Issue 3 (21st August 2014) - Yildirim, Suleyman; Sayit, Muge; Kardas, Geylani; Cortez, Paulo; Santos, Manuel Filipe
Abstract In peer‐to‐peer (P2P) video streaming systems, one of the most challenging parts is to schedule video data dissemination, that is, each peer should carefully select the partner(s) it receives video from and the partner(s) it sends data to. We believe that an agent‐based partner selection approach may improve the quality of streaming by taking both autonomy and dynamic plan selection into account in a goal‐oriented manner. In this study, a Belief‐Desire‐Intention agent architecture for partner selection in P2P video streaming systems is introduced. The major concern of our study is to exhibit how to select the best partner during video streaming session whilst maximizing the quality of video and minimizing delay and hop count. The effects and comparative results of executing proposed agent behaviours are evaluated in the study. The proposed autonomous agent‐based approach also provides an infrastructure in which the best plan for the achievement of optimum streaming goal can be dynamically determined and executed at runtime. Experimental results of the implementation have revealed to us that both of the partner selection methods (with or without agents) manage to increase the video quality. However, the agent‐based approach performs better in terms of received bitrate, delay and hop count during streaming.